2005
DOI: 10.1590/s0103-90162005000600002
|View full text |Cite
|
Sign up to set email alerts
|

Testing and validation of methods for the diagnosis and recomendation integrated system for Signal grass

Abstract: The Diagnosis and Recommendation Integrated System (DRIS) allows the interpretation of results of leaf analysis through relationships among nutrients, instead of the absolute and isolated concentration of each one, as it is used by the criterion of sufficiency range. The objective was to evaluate three procedures of calculation of DRIS indices, and to verify the efficiency of DRIS as interpretation method for the results of Brachiaria decumbens (Signal grass). The study was developed with the results of six ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Elevados coeficientes de variação para os teores de Cu e Zn em plantas de braquiária podem ser uma característica intrínseca desta cultura, tendo em vista que Silveira et al (2005) observaram coeficientes de variação de 106% a 51%, respectivamente, para Cu e Zn, cultivando as plantas em solução nutritiva. As plantas, todavia, seriam indicadoras adequadas da biodisponibilidade desses elementos no sistema (Chen et al, 2010) e nos mapas obtidos (Figura 5).…”
Section: Resultsunclassified
“…Elevados coeficientes de variação para os teores de Cu e Zn em plantas de braquiária podem ser uma característica intrínseca desta cultura, tendo em vista que Silveira et al (2005) observaram coeficientes de variação de 106% a 51%, respectivamente, para Cu e Zn, cultivando as plantas em solução nutritiva. As plantas, todavia, seriam indicadoras adequadas da biodisponibilidade desses elementos no sistema (Chen et al, 2010) e nos mapas obtidos (Figura 5).…”
Section: Resultsunclassified
“…The NBI has been used to prove the effectiveness of the DRIS system in diagnosing the nutritional status of the plant, because the greater the relationship between NBI and yield better the diagnostic system response, to point out the nutritional status of plants (Silveira et al 2005b) (Figure 1). Guindani et al (2009) used the NBI to select the reference population to compose DRIS norms relating to the NBI tracks yield and the yield range that had the highest coefficient of determination (R 2 ) was selected as the reference population.…”
Section: Nutritional Balance Index (Nbi)mentioning
confidence: 99%
“…Guindani et al (2009) used the NBI to select the reference population to compose DRIS norms relating to the NBI tracks yield and the yield range that had the highest coefficient of determination (R 2 ) was selected as the reference population. (F and R values) in the first growth using the norm of the first growth (a), in the first growth using the general norm (b), in the second growth using the norm of the second growth (c) and in the second growth using the general norm (d) (Silveira et al, 2005b).…”
Section: Nutritional Balance Index (Nbi)mentioning
confidence: 99%
“…Nachtigall & Dechen (2007) concluded that the formula developed by Elwali & Gascho (1984) is more efficient than that of Beaufils (1973) or Jones (1981) for apple orchards. On the other hand, Silveira et al (2005) identified the formula proposed by Jones (1981) as more efficient than that of Beaufils (1973) or Elwali & Gascho (1984) for signal grass (Brachiaria). These different conclusions are often related to the type of approach to evaluate the efficiency of the different formulas, e.g, the frequency of the most limiting nutrient and correlation between leaf nutrient levels, without necessarily comparing the diagnostic interpretations with each other.…”
Section: Introductionmentioning
confidence: 97%